Modelling perceived pedestrian level of service of sidewalks: a structural equation approach - Bivina, Geetha Rajendran; Parida, Manoranjan (Transport, 2019)
A disparity between developed and developing countries is not only in the terms of economy and geography, but also on the pedestrians’ perceptions and expectations about the level of service of sidewalks. Therefore, it is paramount to find the effect of various built environment measures, that impact perceived Pedestrian Level Of Service (PLOS) in the context of developing nations. This study investigates the most influential factors of the built environment that affect perceived PLOS of sidewalks in the Indian context. This is one of the first studies in India that utilize Structural Equation Modelling (SEM) technique to assess pedestrian satisfaction and thereby qualitative PLOS of sidewalks. A total of 502 personal interviews was conducted to extract the pedestrian perception about the quality of sidewalks of Thiruvananthapuram city, a typical Indian city. The results identified four latent exogenous constructs named “Safety”, “Security”, “Mobility and infrastructure” and “Comfort and convenience” that represent the main aspects of the PLOS of sidewalks among which factors of security has exhibited highest loading (λ = 0.60). The study identified that parameters like police patrolling, street lighting, cleaner sidewalks, sidewalk obstructions, sidewalk surface have an evident impact on the level of service of sidewalks. The results of the study provide a significant information for interpreting the aspects of the walking environment that mainly influences the PLOS. This information can help city planners to prepare new strategies, policy interventions that enhance the quality of sidewalks and thus making the city more walkable.